Lead-free coating applied to resistor and preparation method of lead-free coating

By combining specific metal oxides with nanomaterials, the lead-free coating is solved, and the resistivity changes caused by corrosion and aging of the resistor are achieved, and good explosion-proof, adhesion and hydrophobic performance are achieved, which extends the service life of the resistor.

CN119752253AActive Publication Date: 2025-04-04SHAANXI OUMGE ELECTRONIC CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510257534.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-04
Estimated Expiration
2045-03-05

AI Technical Summary

Technical Problem

Existing resistors are prone to change in resistivity due to corrosion and aging during long-term use, which affects the stability of the circuit system and may even cause safety accidents.

Method used

A lead-free coating is used to combine materials such as bismuth trioxide, aluminum trioxide, boron trioxide, potassium oxide, calcium fluoride and other materials through cold pressing, ball milling, and heat treatment with grafted nanosilicon dioxide, modified hydroxyethyl cellulose and other materials to make a coating with good explosion-proof, adhesion and hydrophobic properties.

Benefits of technology

The lead-free coating provides good protection on the resistor surface, prevents rust and aging, improves adhesion and service life, and has good hydrophobic properties, is easy to clean, and meets green production requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of lead-free coatings, and discloses a lead-free coating applied to a resistor and a preparation method of the lead-free coating. Bismuth trioxide, aluminum oxide, diboron trioxide, potassium oxide and calcium fluoride are subjected to cold pressing, ball milling and heat treatment to prepare mixed powder. The grafted nano silicon dioxide is formed by grafting hyperbranched polyester prepared from polyester formed by polymerizing acrylic acid, polyurethane and chitosan. The modified hydroxyethyl cellulose is prepared by modifying dodecylpyridinium bromide. The lead-free coating prepared by the invention has good explosion-proof performance, can not explode in the conversion process of low pressure and high pressure, meanwhile, the adhesive force is also greatly improved, the lead-free coating is not easy to fall off in the use process, the service life is prolonged, and the lead-free coating has better hydrophobic performance and is easy to clean. The technology is simple, harmful pollutants are not prone to being generated, and the green production requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lead-free coatings, in particular to a lead-free coating applied to a resistor and a preparation method thereof. Background Art

[0002] Resistors are essential electrical components in circuit systems. There are resistors made of different materials, such as metal resistors, carbon resistors, and ceramic resistors. There are also fixed resistors and variable resistors. Choose the appropriate resistor in different working environments. If exposed resistors, especially metal resistors, are used for a long time, it may cause rust and aging, which will affect the resistivity of the resistor, causing the circuit system to malfunction, and in severe cases may cause safety accidents. Therefore, applying a coating on the surface of the resistor can effectively protect the resistor element, extend its service life, and maintain good performance for a long time, which has positive significance for the entire industry. Summary of the invention

[0003] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a lead-free coating applied to a resistor and a preparation method thereof.

[0004] (II) Technical solution A method for preparing a lead-free coating applied to a resistor comprises the following steps: S1. Mix bismuth trioxide, aluminum trioxide, boron trioxide, potassium oxide and calcium fluoride, and process them by horizontal ball milling at a speed of 200-400 rpm for 1-3 h, cold pressing at a pressure of 10-20 MPa for 2-5 min, and heat treating at a temperature of 420-480°C for 20-40 min. After the treatment, crush and sieve 100-200 mesh to obtain a mixed powder; S2, dissolving chitosan in a 10% by mass glacial acetic acid solution to prepare a chitosan solution, adding liquid polyurethane into water and stirring evenly to prepare a polyurethane solution, heating the chitosan solution to 50-60°C, adding polyurethane solution and acrylic acid, adding initiator ammonium persulfate and initiator manganese ion, heating to 80-90°C, stirring and reacting for 1-3 hours, and obtaining the product acrylic acid polymer; S3, placing diethylenetriamine in an ice water bath, passing nitrogen, slowly adding acrylic acid polymer and methanol, reacting at 20-30°C for 3-6 hours, removing the solvent by vacuum distillation to obtain a reaction monomer, and then mixing it with nano-silica and p-toluenesulfonic acid, stirring at 120-150°C for 8-16 hours under nitrogen, washing the product with methanol, centrifuging at 10000-20000 r / min, and vacuum drying to obtain grafted nano-silica; S4, hydroxyethyl cellulose and isopropanol are mixed and stirred, nitrogen is passed, benzoyl peroxide is slowly added dropwise, and after swelling for 12 to 24 hours, the temperature is raised to 75 to 90°C, dodecylpyridinium bromide is slowly added, and the mixture is reacted for 3 to 6 hours, filtered and washed, neutralized to pH 7 to 8, and vacuum dried to obtain modified hydroxyethyl cellulose; S5. Add the mixed powder, grafted nano-silica and modified hydroxyethyl cellulose into deionized water, stir evenly, add aluminum dihydrogen phosphate, and ball mill for 30 to 60 minutes to prepare a lead-free coating.

[0005] Preferably, in step S1, the mass ratio of bismuth trioxide, aluminum trioxide, boron trioxide, potassium oxide, and calcium fluoride is 1:0.8~1.2:0.8~1.2:0.2~0.4:0.1~0.3.

[0006] Preferably, in step S2, the mass ratio of chitosan, liquid polyurethane, acrylic acid, ammonium persulfate and manganese ion is 1:2~4:0.6~1:0.1~0.3:0.1~0.3.

[0007] Preferably, in step S3, the mass ratio of diethylenetriamine, acrylic acid polymer, methanol, nano-silica and p-toluenesulfonic acid is 1:0.8~1.2:1.5~2.5:1~1.5:0.05~0.12.

[0008] Preferably, in step S4, the mass ratio of hydroxyethyl cellulose, isopropyl alcohol, benzoyl peroxide and dodecylpyridinium bromide is 1:0.6-0.8:0.05-0.2:0.6-0.8.

[0009] Preferably, in step S5, the mass ratio of the mixed powder, grafted nano-silica, modified hydroxyethyl cellulose, deionized water, and aluminum dihydrogen phosphate is 1:0.2~0.4:0.6~0.8:1.2~2.5:0.1~0.3.

[0010] Preferably, the lead-free coating is applied to various types of resistors.

[0011] Preferably, the lead-free coating is uniformly applied to the surface of the resistor, and after coating, it is subjected to a thermal curing treatment at 200-500° C. for 1-3 h.

[0012] 3. Beneficial technical effects The lead-free coating of the present invention is made of bismuth trioxide, aluminum trioxide, boron trioxide, potassium oxide, calcium fluoride, grafted nano silicon dioxide, modified hydroxyethyl cellulose, aluminum dihydrogen phosphate and deionized water. Bismuth trioxide, aluminum trioxide, boron trioxide, potassium oxide and calcium fluoride are cold pressed, ball milled and heat treated to obtain a mixed powder. Grafted nano silicon dioxide is grafted by hyperbranched polymer ester obtained by polymerizing acrylic acid, polyurethane and chitosan. Modified hydroxyethyl cellulose is modified by dodecylpyridinium bromide.

[0013] The lead-free coating prepared by the present invention has good explosion-proof performance, can avoid explosion during the conversion process between low pressure and high pressure, and at the same time, the adhesion is greatly improved, it is not easy to fall off during use, the service life is increased, and it has good hydrophobic performance and is easy to clean. The process of the present invention is simple, it is not easy to produce harmful pollutants, and it meets the requirements of green production. DETAILED DESCRIPTION

[0014] Example 1: S1. 10 kg of bismuth trioxide, 8 kg of aluminum trioxide, 8 kg of boron trioxide, 2 kg of potassium oxide, and 1 kg of calcium fluoride were mixed, and processed by horizontal ball milling at a speed of 200 rpm for 1 h, cold pressing at a pressure of 10 MPa for 2 min, and then heat treated at a temperature of 420°C for 20 min. After the treatment, the mixture was crushed and sieved through 100 mesh to obtain a mixed powder.

[0015] S2. Dissolve 5 kg of chitosan in 30 L of 10% glacial acetic acid solution to prepare a chitosan solution. Add 10 kg of liquid polyurethane to 30 L of water and stir evenly to prepare a polyurethane solution. Heat the chitosan solution to 50°C, add the polyurethane solution and 3 kg of acrylic acid, add 0.5 kg of initiator ammonium persulfate and 0.5 kg of initiator manganese ion, heat to 80°C, stir and react for 1 h to obtain the product acrylic acid polymer.

[0016] S3. Place 10 kg of diethylenetriamine in an ice-water bath, pass nitrogen, slowly drop 8 kg of acrylic acid polymer and 15 kg of methanol, react at 20°C for 3 h, remove the solvent by vacuum distillation to obtain a reaction monomer, then mix it with 10 kg of nano-silica and 0.5 kg of p-toluenesulfonic acid, stir at high speed at 120°C for 8 h under nitrogen, wash the product with methanol, centrifuge at 10,000 r / min, and vacuum dry to obtain grafted nano-silica.

[0017] S4. Mix 10 kg of hydroxyethyl cellulose and 6 kg of isopropanol, and stir. Pass nitrogen. Slowly drop 0.5 kg of benzoyl peroxide. After swelling for 12 hours, heat to 75°C, slowly add 6 kg of dodecylpyridinium bromide, react for 3 hours, filter and wash, neutralize to pH 7, and vacuum dry to obtain modified hydroxyethyl cellulose.

[0018] S5. Add 10 kg of mixed powder, 2 kg of grafted nano-silica, and 6 kg of modified hydroxyethyl cellulose into 12 kg of deionized water, stir evenly, add 1 kg of aluminum dihydrogen phosphate, and ball mill for 30 min to prepare a lead-free coating.

[0019] Example 2: S1. 10 kg of bismuth trioxide, 12 kg of aluminum trioxide, 12 kg of boron trioxide, 4 kg of potassium oxide, and 3 kg of calcium fluoride were mixed, and processed by horizontal ball milling at a speed of 400 rpm for 3 h, cold pressing at a pressure of 20 MPa for 5 min, and then heat treated at a temperature of 480°C for 40 min. After the treatment, the mixture was crushed and sieved through 200 mesh to obtain a mixed powder.

[0020] S2. Dissolve 5 kg of chitosan in 60 L of 10% glacial acetic acid solution to prepare a chitosan solution. Add 20 kg of liquid polyurethane to 60 L of water and stir evenly to prepare a polyurethane solution. Heat the chitosan solution to 60°C, add the polyurethane solution and 5 kg of acrylic acid, add 1.5 kg of initiator ammonium persulfate and 1.5 kg of initiator manganese ions, raise the temperature to 90°C, stir and react for 3 h to obtain the product acrylic acid polymer.

[0021] S3. Place 10 kg of diethylenetriamine in an ice-water bath, pass nitrogen, slowly drop 12 kg of acrylic acid polymer and 25 kg of methanol, react at 30°C for 6 h, remove the solvent by vacuum distillation to obtain a reaction monomer, then mix it with 15 kg of nano-silica and 1.2 kg of p-toluenesulfonic acid, stir at 150°C for 16 h under nitrogen, wash the product with methanol, centrifuge at 20,000 r / min, and vacuum dry to obtain grafted nano-silica.

[0022] S4. Mix 10 kg of hydroxyethyl cellulose and 8 kg of isopropanol, and stir. Pass nitrogen. Slowly drop 2 kg of benzoyl peroxide. After swelling for 24 hours, heat to 90°C, slowly add 8 kg of dodecylpyridinium bromide, react for 6 hours, filter and wash, neutralize to pH 8, and vacuum dry to obtain modified hydroxyethyl cellulose.

[0023] S5. Add 10 kg of mixed powder, 4 kg of grafted nano-silica, and 8 kg of modified hydroxyethyl cellulose into 25 kg of deionized water, stir evenly, add 3 kg of aluminum dihydrogen phosphate, and ball mill for 60 min to prepare a lead-free coating.

[0024] Example 3: S1. 10 kg of bismuth trioxide, 9 kg of aluminum trioxide, 10 kg of boron trioxide, 3 kg of potassium oxide, and 2 kg of calcium fluoride were mixed, and processed by horizontal ball milling at a speed of 300 rpm for 1.5 h, cold pressing at a pressure of 12 MPa for 3 min, and then heat treated at a temperature of 450°C for 30 min. After the treatment, the mixture was crushed and sieved through 120 mesh to obtain a mixed powder.

[0025] S2. Dissolve 5 kg of chitosan in 40 L of 10% glacial acetic acid solution to prepare a chitosan solution. Add 12 kg of liquid polyurethane to 4 L of water and stir evenly to prepare a polyurethane solution. Heat the chitosan solution to 55°C, add the polyurethane solution and 3.5 kg of acrylic acid, add 0.8 kg of initiator ammonium persulfate and 0.6 kg of initiator manganese ion, raise the temperature to 90°C, stir and react for 2 h to obtain the product acrylic acid polymer.

[0026] S3. Place 10 kg of diethylenetriamine in an ice-water bath, pass nitrogen, slowly drop 10 kg of acrylic acid polymer and 18 kg of methanol, react at 25°C for 4 h, remove the solvent by vacuum distillation to obtain a reaction monomer, then mix it with 12 kg of nano-silica and 0.6 kg of p-toluenesulfonic acid, stir at 130°C for 10 h under nitrogen, wash the product with methanol, centrifuge at 15000 r / min, and vacuum dry to obtain grafted nano-silica.

[0027] S4. Mix 10 kg of hydroxyethyl cellulose and 6.5 kg of isopropanol, and stir. Pass nitrogen. Slowly drop 0.9 kg of benzoyl peroxide. After swelling for 15 hours, heat to 80°C, slowly add 6.2 kg of dodecylpyridinium bromide, react for 4 hours, filter and wash, neutralize to pH 8, and vacuum dry to obtain modified hydroxyethyl cellulose.

[0028] S5. Add 10 kg of mixed powder, 2.5 kg of grafted nano-silica, and 7.2 kg of modified hydroxyethyl cellulose into 18 kg of deionized water, stir evenly, add 1.2 kg of aluminum dihydrogen phosphate, and ball mill for 50 min to prepare a lead-free coating.

[0029] Example 5: S1. Mix 10 kg of bismuth trioxide, 10.3 kg of aluminum trioxide, 11.5 kg of boron trioxide, 3.5 kg of potassium oxide, and 2.2 kg of calcium fluoride, and process them by horizontal ball milling at a speed of 300 rpm for 2.5 h, cold pressing at a pressure of 16 MPa for 5 min, and then heat treating at a temperature of 460°C for 30 min. After the treatment, crush and sieve through 160 mesh to obtain a mixed powder.

[0030] S2. Dissolve 5 kg of chitosan in 50 L of 10% glacial acetic acid solution to prepare a chitosan solution. Add 18 kg of liquid polyurethane to 45 L of water and stir evenly to prepare a polyurethane solution. Heat the chitosan solution to 50°C, add the polyurethane solution and 4.5 kg of acrylic acid, add 1 kg of initiator ammonium persulfate and 1 kg of initiator manganese ions, raise the temperature to 80°C, stir and react for 1.5 h to obtain the product acrylic acid polymer.

[0031] S3. Place 10 kg of diethylenetriamine in an ice-water bath, pass nitrogen, slowly drop 10.5 kg of acrylic acid polymer and 20 kg of methanol, react at 30°C for 5 h, remove the solvent by vacuum distillation to obtain a reaction monomer, then mix it with 14 kg of nano-silica and 0.9 kg of p-toluenesulfonic acid, stir at 140°C for 15 h under nitrogen, wash the product with methanol, centrifuge at 18000 r / min, and vacuum dry to obtain grafted nano-silica.

[0032] S4. Mix 10 kg of hydroxyethyl cellulose and 7.5 kg of isopropanol, and stir. Pass nitrogen. Slowly drop 1.2 kg of benzoyl peroxide. After swelling for 20 hours, heat to 80°C, slowly add 7.5 kg of dodecylpyridinium bromide, react for 5 hours, filter and wash, neutralize to pH 7, and vacuum dry to obtain modified hydroxyethyl cellulose.

[0033] S5. Add 10 kg of mixed powder, 3.5 kg of grafted nano-silica, and 7.5 kg of modified hydroxyethyl cellulose into 20 kg of deionized water, stir evenly, add 2.5 kg of aluminum dihydrogen phosphate, and ball mill for 50 min to prepare a lead-free coating.

[0034] Example 5: S1. Mix 10 kg of bismuth trioxide, 11.2 kg of aluminum trioxide, 10.5 kg of boron trioxide, 3.5 kg of potassium oxide, and 2.3 kg of calcium fluoride, and process them by horizontal ball milling at a speed of 350 rpm for 3 h, cold pressing at a pressure of 20 MPa for 5 min, and then heat treating at a temperature of 460°C for 40 min. After the treatment, crush and sieve through 200 mesh to obtain a mixed powder.

[0035] S2. Dissolve 5 kg of chitosan in 45 L of 10% glacial acetic acid solution to prepare a chitosan solution. Add 20 kg of liquid polyurethane to 30 L of water and stir evenly to prepare a polyurethane solution. Heat the chitosan solution to 60°C, add the polyurethane solution and 4 kg of acrylic acid, add 1.3 kg of initiator ammonium persulfate and 1.2 kg of initiator manganese ions, raise the temperature to 90°C, stir and react for 3 h to obtain the product acrylic acid polymer.

[0036] S3. Place 10 kg of diethylenetriamine in an ice-water bath, pass nitrogen, slowly drop 10.2 kg of acrylic acid polymer and 22 kg of methanol, react at 30°C for 5 h, remove the solvent by vacuum distillation to obtain a reaction monomer, then mix it with 15 kg of nano-silica and 0.5 kg of p-toluenesulfonic acid, stir at 150°C for 15 h under nitrogen, wash the product with methanol, centrifuge at 20,000 r / min, and vacuum dry to obtain grafted nano-silica.

[0037] S4. Mix 10 kg of hydroxyethyl cellulose and 8 kg of isopropanol, and stir. Pass nitrogen. Slowly drop 0.5 kg of benzoyl peroxide. After swelling for 24 hours, heat to 90°C, slowly add 8 kg of dodecylpyridinium bromide, react for 3 hours, filter and wash, neutralize to pH 7, and vacuum dry to obtain modified hydroxyethyl cellulose.

[0038] S5. Add 10 kg of mixed powder, 3 kg of grafted nano-silica, and 8 kg of modified hydroxyethyl cellulose into 15 kg of deionized water, stir evenly, add 2 kg of aluminum dihydrogen phosphate, and ball mill for 50 min to prepare a lead-free coating.

[0039] Comparative Example 1: 5 kg of aluminum dihydrogen phosphate was added to 8 kg of deionized water, stirred evenly, and ball milled for 30 min to prepare a coating.

[0040] Test Example 1: Overvoltage Test Test method: Take AC 220 V as the starting point and maintain for 1 min, quickly increase to the starting voltage and the center voltage of 270 V of the maximum allowable AC voltage of 320 V within 2 s and maintain for 1 min, then quickly increase to the maximum allowable AC voltage of 320 V within 2 s and maintain for 2 min, then increase the voltage at a rate of 10 V every 30 s until the varistor test fails, and observe the spark, burning or bursting of the varistor. Among them, the specification of the fuse is 5 A slow type. If the varistor has sparks, burning, or bursting, it is judged that the overvoltage test has not passed, which is represented by "X"; if the varistor has no sparks, burning, or bursting, it is judged that the overvoltage test has passed, which is represented by "O" in the following Table 3.

[0041] Table 1

[0042] It can be seen from Table 1 that the lead-free coatings of Examples 1 to 5 have good explosion-proof properties and will not generate sparks or burners when subjected to transient voltage.

[0043] Test Example 2: Adhesion Test Test method: The cross-hatch method was used as the test method. According to GB / T9286-2021, the coatings prepared in Examples 1 to 5 and Comparative Example 1 were coated on a 200 mm × 200 mm × 10 mm carbon steel plate for testing. A 6 × 6 cutting method was used. Three parts of the coating of each sample were selected to make cutting samples. The overall situation was observed, and the adhesion index of the coating was evaluated according to the standard. The results are shown in Table 2. Table 2

[0044] It can be seen from Table 2 that the coatings of Examples 1 to 5 have good adhesion and are not easy to fall off.

[0045] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a lead-free coating for a resistor, characterized in that: The following steps are involved: S1. Mix bismuth trioxide, aluminum trioxide, boron trioxide, potassium oxide and calcium fluoride, and process them by horizontal ball milling at a speed of 200-400 rpm for 1-3 h, cold pressing at a pressure of 10-20 MPa for 2-5 min, and heat treating at a temperature of 420-480°C for 20-40 min. After the treatment, crush and sieve 100-200 mesh to obtain a mixed powder; S2, dissolving chitosan in a 10% by mass glacial acetic acid solution to prepare a chitosan solution, adding liquid polyurethane into water and stirring evenly to prepare a polyurethane solution, heating the chitosan solution to 50-60°C, adding polyurethane solution and acrylic acid, adding initiator ammonium persulfate and initiator manganese ion, heating to 80-90°C, stirring and reacting for 1-3 hours, and obtaining the product acrylic acid polymer; S3, placing diethylenetriamine in an ice water bath, passing nitrogen, slowly adding acrylic acid polymer and methanol, reacting at 20-30°C for 3-6 hours, removing the solvent by vacuum distillation to obtain a reaction monomer, and then mixing it with nano-silica and p-toluenesulfonic acid, stirring at 120-150°C for 8-16 hours under nitrogen, washing the product with methanol, centrifuging at 10000-20000 r / min, and vacuum drying to obtain grafted nano-silica; S4, hydroxyethyl cellulose and isopropanol are mixed and stirred, nitrogen is passed, benzoyl peroxide is slowly added dropwise, and after swelling for 12 to 24 hours, the temperature is raised to 75 to 90°C, dodecylpyridinium bromide is slowly added, and the mixture is reacted for 3 to 6 hours, filtered and washed, neutralized to pH 7 to 8, and vacuum dried to obtain modified hydroxyethyl cellulose; S5. Add the mixed powder, grafted nano-silica and modified hydroxyethyl cellulose into deionized water, stir evenly, add aluminum dihydrogen phosphate, and ball mill for 30 to 60 minutes to prepare a lead-free coating.

2. The method for preparing a lead-free coating for a resistor according to claim 1, characterized in that: In the step S1, the mass ratio of bismuth trioxide, aluminum trioxide, boron trioxide, potassium oxide and calcium fluoride is 1:0.8~1.2:0.8~1.2:0.2~0.4:0.1~0.

3.

3. The method for preparing a lead-free coating for a resistor according to claim 1, characterized in that: In step S2, the mass ratio of chitosan, liquid polyurethane, acrylic acid, ammonium persulfate and manganese ion is 1:2-4:0.6-1:0.1-0.3:0.1-0.

3.

4. The method for preparing a lead-free coating for a resistor according to claim 1, characterized in that: In the step S3, the mass ratio of diethylenetriamine, acrylic acid polymer, methanol, nano-silicon dioxide and p-toluenesulfonic acid is 1:0.8~1.2:1.5~2.5:1~1.5:0.05~0.

12.

5. The method for preparing a lead-free coating for a resistor according to claim 1, characterized in that: In step S4, the mass ratio of hydroxyethyl cellulose, isopropyl alcohol, benzoyl peroxide and dodecylpyridinium bromide is 1:0.6-0.8:0.05-0.2:0.6-0.

8.

6. The method for preparing a lead-free coating for a resistor according to claim 1, characterized in that: In the step S5, the mass ratio of the mixed powder, grafted nano-silica, modified hydroxyethyl cellulose, deionized water, and aluminum dihydrogen phosphate is 1:0.2-0.4:0.6-0.8:1.2-2.5:0.1-0.

3.

7. An application of the lead-free coating prepared by the method for preparing a lead-free coating for a resistor as claimed in claim 1, characterized in that: The lead-free coating is applied to various types of resistors.

8. The use of the lead-free coating according to claim 7, characterized in that: The lead-free coating is evenly applied to the surface of the resistor. After coating, it is subjected to thermal curing treatment at 200~500℃ for 1~3 hours.

Citation Information

Patent Citations

  • Antibacterial antistatic emulsion and coating and their preparation method

    CN106117415A

  • Preparation method of lightning arrester zinc oxide pressure-sensitive valve plate ceramic precursor

    CN111925206A

  • Inorganic resistive coating and its preparation method

    CN1138201A

  • Preparation method of thermistor coating

    CN115762939A

  • Active energy ray-curable antistatic coating composition

    EP1302514A2